Ischemia and Anatomy in the New 2024 European Guidelines for Chronic Coronary Syndromes: Update and Comparison of Recommendations - Caroli, Christian A (Journal Of The Saudi Heart Association, 2025)
The new 2024 European guideline on chronic coronary syndromes (CCS) is a pivotal document for clinical practice, updating the evidence and indications after five years, incorporating insights from the paradigm-shifting ISCHEMIA trial. This article explores the evolving role of functional and anatomical testing in assessing coronary artery disease (CAD), highlighting the introduction of a new risk probability score based on clinical and risk factors. Additionally, it provides a detailed comparison between these European recommendations and those from the most influential American guidelines, emphasizing key differences in the approach to risk stratification and diagnostic strategies. This comprehensive analysis provides valuable insights for optimizing the management of a syndrome that, in light of new evidence, has proven to be clinically complex and, in many aspects, counterintuitive.